2020
DOI: 10.1002/dev.21981
|View full text |Cite
|
Sign up to set email alerts
|

Biological sensitivity to context in Pakistani preschoolers: Hair cortisol and family wealth are interactively associated with girls’ cognitive skills

Abstract: Children's stress physiology can shed light on which children are more or less susceptible to contextual experiences (Obradović, 2016). Over the last decade, researchers have identified concentrations of the stress hormone cortisol in the hair shaft as a promising biomarker indexing the long-term, chronic impact of adversity on functioning of the hypothalamic-pituitary-adrenal (HPA) axis (Bates, Salsberry, & Ford, 2017). However, links between hair cortisol concentrations (HCCs), adversity, and young children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…The current study does not evaluate the impact of the intervention; those results have already been published (see Yousafzai et al, 2014; Yousafzai et al, 2016). Rather, the current study controls for the impact of the intervention while evaluating the longitudinal link between home stimulation and motor skills, consistent with other published papers in this sample (Armstrong-Carter et al, 2020; Finch et al, 2018; Obradović et al, 2016).…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The current study does not evaluate the impact of the intervention; those results have already been published (see Yousafzai et al, 2014; Yousafzai et al, 2016). Rather, the current study controls for the impact of the intervention while evaluating the longitudinal link between home stimulation and motor skills, consistent with other published papers in this sample (Armstrong-Carter et al, 2020; Finch et al, 2018; Obradović et al, 2016).…”
Section: Methodssupporting
confidence: 74%
“…Following a precedent set by published studies of developmental processes using this birth-cohort (Armstrong-Carter et al, 2020; Finch et al, 2018; Jeong et al, 2019; Obradović et al, 2019; Obradovic et al, 2016; Tarullo et al, 2017), our analysis used the full sample, which is more representative of the study population and retains greater statistical power for our complex, longitudinal models (compared with the control group alone), and controlled for intervention conditions. We tested a series of four linear regression models to investigate direct associations of prior home stimulation (Models 1 and 2) and concurrent home stimulation (Models 3 and 4) with children’s motor skills at age 4.…”
Section: Methodsmentioning
confidence: 99%
“…HCC, however, was significantly negatively related to EF, consistent with studies of adults where acute and cumulative measures of cortisol were negatively related to EF (Assayag et al., 2017; Shields et al., 2016). In children, the direction of associations between HCC and EF‐related constructs like ADHD symptoms, behavior problems, and cognitive skills have been mixed (e.g., Armstrong‐Carter et al., 2020; Golub et al., 2019; Pauli‐Pott et al., 2019; Schloß et al., 2018). Here, we found a marginal difference by age group such that higher HCC predicted worse EF for younger (<9.7 years) but not older children.…”
Section: Discussionmentioning
confidence: 99%
“…In children, HCC is associated with related constructs; higher HCC predicts fewer ADHD symptoms (Pauli‐Pott et al., 2019; Schloß et al., 2018) but also more behavior problems (Golub et al., 2019). A recent study of Pakistani preschoolers found a negative association between HCC and cognitive skills including EF, but only for girls with higher family wealth (Armstrong‐Carter et al., 2020). Generally, lower socioeconomic status and exposure to more poverty‐related stressors like household chaos, maternal distress, and overall perceived stress are associated with increased HCC in adults (O'Brien et al., 2013) and children (Andrews, 2020; Vliegenthart et al., 2016), although some results have been mixed (Gray et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation